Child health and unhealthy sanitary practices in India: Evidence from Recent Round of National Family Health Survey-IV. (April 2019) - Dwivedi, Laxmi Kant; Banerjee, Kajori; Jain, Nidhi; Ranjan, Mukesh; Dixit, Priyanka
Abstract: Objectives: Despite threefold increase in investment (from Rs. 28, 500 million to Rs. 90, 000 million during 2014–17) in the allocation of funds for the Clean India movement, creating awareness and various social movements, more than half of the rural population (52.1%) of the country still defecates in the open. This study aims to examine the prevalence of improved sanitation facilities and safe stool disposal in India and its states. It also aims to further establish inter-linkages between safe stool disposal and child health. Study design: The present study uses data from the fourth round of the recently conducted cross-sectional National Family Health Survey (NFHS-4, 2015–16). Methods: Two proxy indicators used to assess the effect on child health are: stunting and mortality of children under the age of five years. Multivariate logistic regression analysis was employed to examine the impact of improved sanitation facilities and safe stool disposal on child health measured by height-for-age as a dichotomous variable. Multivariate discrete-time logistic model was used to examine the impact of improved sanitation facilities and safe stool disposal on under-five child deaths. Results: The results reveal that unsafe disposal of stools are one of the main contributing factors responsible for stunting and under-five mortality among children. The prevalence was clearly seen to be higher in households where open defecation and unsafe stool disposal were practised. Conclusions: The central behavioural change to be brought about among the people is to improve the cleanliness levels of the neighbourhood and help children spend their childhood free from the misery of malnourishment or in the worst case, death. It is not an impossible task for a country that houses the cleanest village in Asia, Mawlynnong in the Northeast state of Meghalaya, India. If one state could do it, it could be replicated in other states too. Highlights: The study estimates the advantage of practicing safe and hygienic sanitation in terms of reduction in the number of stunted children and under-five child deaths from NFHS 4, 2015-16. The odds of under-five mortality due to open defecation and unsafe stool disposal practices is 1.20 and 1.39, respectively. If all the households in India practice safe stool disposal of children, there can be a significant reduction in under-five child mortality.